Transient Response of a Plate-Fluid System to Stationary and Moving Pressure Loads - Norwood, F.R.; Warren, W.E. (Engineering Transactions, 1975)
Bernoulli-Euler plate theory, in conjunction with Laplace and Fourier transforms, is utilized to investigate possible wave motion in a fluid half-space which supports an infinite plate. The surface of the plate is subjected to time and space dependent loadings. Two specific loading conditions are considered, one stationary and one moving, and wave front approximations for the disturbance in the fluid are obtained pressure. Limitations on previous steady-state analysis are pointed out. Results are compared with those obtained in the absence of the plate. Within the framework of this theory, the presence of the plate weakens the pressure wave front over that in the plane fluid half-space.